2010
DOI: 10.1021/es102033k
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Airborne Perfluorinated Compounds during Professional Ski Waxing

Abstract: The concentration levels of 11 perfluorinated carboxylic (PFCA) and eight sulfonic (PFSA) acids were determined in the serum of 13 professional ski waxers. The same components were also determined in workroom aerosols and in fluoro containing solid ski waxes and ski wax powders. The highest median concentration (50 ng/mL) was detected for perfluorooctanoic acid (PFOA), which is around 25 times higher than the background level. For the first time perfluorotetradecanoic acid (PFTeDA) has been found in human seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(123 citation statements)
references
References 27 publications
7
116
0
Order By: Relevance
“…The half-life range for PFOA was later confirmed in studies of general populations from Germany and the US exposed to PFOA through contaminated drinking water (Bartell et al 2009;Hölzer et al 2009;Seals et al 2010). Two recent studies on exposures of professional ski waxing technicians indicated long elimination half-lives for PFNA, PFDA and PFUnDA as well (Freberg et al 2010;Nilsson et al 2010). In contrast the half-life of PFBS in six occupationally exposed workers was found to be around one month (Olsen et al 2009a).…”
Section: Physical-chemical Properties and Pharmacokineticsmentioning
confidence: 90%
See 1 more Smart Citation
“…The half-life range for PFOA was later confirmed in studies of general populations from Germany and the US exposed to PFOA through contaminated drinking water (Bartell et al 2009;Hölzer et al 2009;Seals et al 2010). Two recent studies on exposures of professional ski waxing technicians indicated long elimination half-lives for PFNA, PFDA and PFUnDA as well (Freberg et al 2010;Nilsson et al 2010). In contrast the half-life of PFBS in six occupationally exposed workers was found to be around one month (Olsen et al 2009a).…”
Section: Physical-chemical Properties and Pharmacokineticsmentioning
confidence: 90%
“…Increased PFOA concentrations have also been observed in a population living close to a manufacturing site (Emmett et al 2006). Further, two Nordic studies have seen elevated concentrations of PFCAs in serum from professional skiwaxers (Freberg et al 2010;Nilsson et al 2010). No clear regional differences have been observed for general populations.…”
Section: Human Biomonitoring (Internal Dose)mentioning
confidence: 96%
“…The measured PFAS composition compared to the composition of snow from skiing regions subjected to ski waxes (Freberg et al, 2010) suggests that direct contamination from human activities (skiing, sampling campaigns) is negligible for the sampling location. We therefore assume that PFAS contamination has completely resulted from atmospheric wet and dry deposition.…”
Section: Sources Of Pfassmentioning
confidence: 96%
“…Time trend studies show that PFOA levels are significantly associated with the time being exposed to PFOA, i.e. during work as a ski waxer [102][103][104]. And recent studies strongly indicate that PFOA levels increase with age [105,106].…”
Section: Assessment Of the Bioaccumulation Potentialmentioning
confidence: 99%